Effect of anodic polarization treatment on microbiologically influenced corrosion resistance of Cu-bearing stainless steel against marine Pseudomonas aeruginosa. (October 2022) - Zhao, Jin-Long; Sun, Da; Arroussi, Mohammed; Lian, Tong-Yu; Zhang, Xin-Rui; Yang, Chun-Guang; Yang, Ke
Abstract: Anodic polarization treatment was used to investigate microbiologically influenced corrosion (MIC) behavior of 316 L -Cu stainless steel (SS) against marine Pseudomonas aeruginosa using electrochemical tests and morphology observation techniques. The results indicated that anodic polarization treatment endowed 316 L -Cu SS with a decreased corrosion current and increased pitting potential in comparison with conventional 316 L SS and 316 L -Cu SS incubated in a biotic medium. The surface morphology observations combined with XPS analysis found that 316 L -Cu SS effectively inhibited bacterial reproduction and promoted the formation of a dense protective extracellular polymeric substance (EPS)-Fe membrane, leading to less susceptibility to pitting corrosion than 316 L SS. Graphical Abstract: ga1 Highlights: Anodic polarization treatment (APT) on MIC behavior of stainless steel is studied. APT regulates the attachment of Pseudomonas aeruginosa with negative charge. APT promotes the formation of EPS-Fe membrane with protective effect. Cu-bearing SS combined with EPS-Fe membrane can continuously inhibit MIC.